Upward social comparison on network and alcohol dependence in college students: the chain mediation impacts of relative deprivation and anxiety - Shuna Li; Kaijie Zhang; Kaizhen Kong; Hua Niu; Zhenli Jiang; Hongbo Guo (BMC Psychology)
Abstract Background Nowadays, contemporary society has placed growing emphasis on the alcohol drinking behavior of college students. Methods This study employed a cross-sectional design to assess the relationship between upward social comparison (USC) on network and college students drinking behavior, while exploring the mediation impact of relative deprivation (RD) and anxiety. A total of 329 college students (Mage = 21.37 years old; 16.11% women) were enrolled to complete a set of questionnaires evaluating USC on network, RD, anxiety and alcohol dependence. Results The results showed that (1) USC on network, RD, anxiety and alcohol dependence were significantly, positively correlated in pairs, and (2) RD and anxiety exhibited a significant chain mediating role between USC on network and alcohol dependence, and USC on network positively predicted alcohol dependence via the mediating effect of anxiety. Conclusions This study reveals that USC on network positively predicts alcohol dependence via the mediating effect of anxiety, and that RD and anxiety play a chain-mediating role between USC on network and alcohol dependence.